Neither plasma progesterone concentrations nor exogenous eCG affects rates of ovulation or pregnancy in fixed-time artificial insemination (FTAI) protocols for puberal Nellore heifers - Pegorer, M. Figueira; Ereno, R. L.; Satrapa, R. A.; Pinheiro, V. G.; Trinca, L. A.; Barros, C. M. (Elsevier, 2011)
The objective was to evaluate the effects of plasma progesterone (P4) concentrations and exogenous eCG on ovulation and pregnancy rates of pubertal Nellore heifers in fixed-time artificial insemination (FTAI) protocols. In Experiment 1 (Exp. 1), on Day 0 (7 d after ovulation), heifers (n = 15) were given 2 mg of estradiol benzoate (EB) im and randomly allocated to receive: an intravaginal progesterone-releasing device containing 0.558 g of P4 (group 0.5G, n = 4); an intravaginal device containing 1 g of P4 (group 1G, n = 4); 0.558 g of P4 and PGF2α (PGF; 150 μg d-cloprostenol, group 0.5G/PGF, n = 4); or 1 g of P4 and PGF (group 1G/PGF, n = 3). On Day 8, PGF was given to all heifers and intravaginal devices removed; 24 h later (Day 9), all heifers were given 1 mg EB im. In Exp. 2, pubertal Nellore heifers (n = 292) were treated as in Exp. 1, with FTAI on Day 10 (30 to 36 h after EB). In Exp. 3, pubertal heifers (n = 459) received the treatments described for groups 0.5G/PGF and 1G/PGF and were also given 300 IU of eCG im (groups 0.5G/PGF/eCG and 1G/PGF/eCG) at device removal (Day 8). In Exp. 1, plasma P4 concentrations were significantly higher in heifers that received 1.0 vs 0.588 g P4, and were significantly lower in heifers that received PGF on Day 0. In Exp. 2 and 3, there were no significant differences among groups in rates of ovulation (65-77%) or pregnancy (Exp. 2: 26-33%; Exp. 3: 39-43%). In Exp. 3, diameter of the dominant ovarian follicle on Day 9 was larger in heifers given 0.558 g vs 1.0 g P4 (10.3 ± 0.2 vs 9.3 ± 0.2 mm; P < 0.01). In conclusion, lesser amounts of P4 in the intravaginal device or PGF on Day 0 decreased plasma P4 from Days 1 to 8 and increased diameter of the dominant follicle on Day 9. However, neither of these nor 300 IU of eCG on Day 8 significantly increased rates of ovulation or pregnancy. © 2011.
Keywords: Bos indicus; Fixed-time artificial insemination; Nellore heifers; Progesterone; chorionic gonadotropin; drug derivative; estradiol; estradiol 3-benzoate; estradiol benzoate; progesterone; prostaglandin F; animal; animal disease; artificial insemination; blood; cattle; clinical trial; controlled clinical trial; controlled study; drug effect; female; methodology; ovulation; ovulation induction; physiology; pregnancy; pregnancy rate; randomized controlled trial; Animals; Cattle; Chorionic Gonadotropin; Estradiol; Female; Insemination, Artificial; Ovulation; Ovulation Induction; Pregnancy; Pregnancy Rate; Prostaglandins F